To bring the distant near: On deixis in Iranian oral literature - Jahani, Carina (Trends in Iranian and Persian Linguistics, 2018)
The purpose of this article is to study oral narratives in a number of Iranian languages with a particular focus on how the audience is brought inside the framework of the story. The oral narratives selected for this study are traditional folktales and legends in Koroshi Balochi, Sistani Balochi, Vafsi, and Gorani. Deictic devices locate an event and its participants in time and space and cannot be fully interpreted without reference to the context. They also bring coherence to the narrative. A deictic center is a point to which the deictic element is anchored. Deixis can be absolute, i.e., place the deictic center at the location and moment of utterance, but the speaker does not necessarily need to adopt his or her own time and location as the deictic center. It is also possible to detach the deictic center completely from not only the temporal and locational setting of the speech, but also from the real world, and to place it at a time and place that never existed or will exist inside an imaginary story (deictic shift). The four linguistic variants in this study show interesting variation when it comes to deictic shift. It is more common for spatial deixis to be shifted to the story than for tense to be anchored in the story. Koroshi Balochi, Sistani Balochi, and Vafsi present almost total spatial deictic shift, whereas in Gorani the deixis is occasionally moved outside the story. Gorani is the language that has the strongest tense anchoring inside the narrative, with almost exclusive use of the non-past tense. At the other extreme we find Sistani Balochi, which has no tense anchoring in the narrative (only past tense verb forms). Koroshi Balochi uses non-past tense for events in the story line and Vafsi changes between using non-past and past tense.